In situ gas/solid reaction for the formation of luminescent quantum confined CH3NH3PbBr3 perovskite planar film. Issue 74 (19th August 2016) - Zhang, Taiyang; Li, Ge; Xu, Feng; Wang, Yipeng; Guo, Nanjie; Qian, Xufang; Zhao, Yixin
Abstract : We demonstrate a facile gas solid reaction of PbBr2 film with CH3 NH2 gas under ambient conditions to form a luminescent quantum confined CH3 NH3 PbBr3 perovskite film. Abstract : We demonstrate a new strategy for the in situ formation of highly luminescent CH3 NH3 PbBr3 perovskite planar film via the reaction between PbBr2 and methylamine gas. The obtained CH3 NH3 PbBr3 perovskite planar film exhibited similar quantum confinement to solution chemistry synthesized colloidal CH3 NH3 PbBr3 quantum dots. Such quantum confinement was realized by a PbO x /Pb(OH)2 framework, which is a by-product formed in situ from the reaction of PbBr2 and methylamine gas under ambient conditions.